2007
DOI: 10.1159/000104761
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Photodynamic Therapy in the Management of Occult Choroidal Neovascularization Associated with Serous Pigment Epithelium Detachment

Abstract: Aims: To evaluate the efficacy of photodynamic therapy (PDT) in the treatment of subfoveal occult choroidal neovascularization (CNV) associated with serous pigment epithelium detachment (PED) in eyes with age-related macular degeneration. Methods: Hundred and fifty-three patients (161 eyes) with subfoveal occult CNV due to age-related macular degeneration, were divided into two groups. The first group (70 patients, 75 eyes) included eyes with occult CNV associated with serous PED of at least 1 disc diameter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Among the eyes of the Grade 4 group, the functional results remained unchanged, whether treatment was administered (7 eyes) or not (3 eyes). However, two of the seven eyes that were treated (ranibizumab [5] and bevacizumab [2]) had a better anatomical response. These two eyes received ranibizumab as an anti-VEGF treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the eyes of the Grade 4 group, the functional results remained unchanged, whether treatment was administered (7 eyes) or not (3 eyes). However, two of the seven eyes that were treated (ranibizumab [5] and bevacizumab [2]) had a better anatomical response. These two eyes received ranibizumab as an anti-VEGF treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported on the development of RPE tears either spontaneously during the natural course of the disease or as a side effect of various treatments, including thermal laser, photodynamic therapy (PDT), pegaptanib (Macugen; Eyetech Pharmaceuticals, New York, NY), bevacizumab (Avastin; Genentech, Inc, South San Francisco, CA), or ranibizumab (Lucentis, Genentech, Inc). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Even though RPE tear is considered a severe complication associated with significant visual loss, studies have shown that in many cases, the vision may be preserved. [8][9][10][11]15 In our study, we present our anatomical and functional results in patients with RPE tear associated with exudative AMD who were treated with intravitreal ranibizumab injections and followed-up for a median of 1 year.…”
mentioning
confidence: 99%
“…In PDT studies, it has been reported that the VA of patients did not increase and that, in some cases, the patient's VA decreased due to the development of RPE tears, depending on the treatment or the natural course of the disease (14,15) . Consequently, on the basis of the association between PED and inflammation, IVTA treatment was added to the PDT.…”
Section: Discussionmentioning
confidence: 99%
“…2 Treatment options for CNV associated with PED in AMD, such as laser photocoagulation, photodynamic therapy, and/or intravitreal steroids, have been reported but lead to unsatisfactory or conflicting results. 3 There are, as yet, no established treatment recommendations for PED associated with CNV, most likely due to the fact that the development of PED and its natural course in AMD has not yet been fully investigated. In general, treatment of PEDs associated with CNV is particularly difficult due to the risk of development of an RPE tear.…”
Section: Introductionmentioning
confidence: 99%